MODEL PEMBELAJARAN CORE (CONNECTING, ORGANIZING, REFLECTING, AND EXTENDING) BERBANTUAN MACROMEDIA FLASH 8 TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA SMP NEGERI 15 PALEMBANG - Anbar Faridah Ramadhan; Destiniar Destiniar; Putri Fitriasari (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
The purpose of this study was to determine the effect of the CORE learning model assisted  by  Macromedia  Flash  8 on  students'  mathematical  problem  solving abilities. This research method uses Groub Design Posttest-Only Control. The population in this study were all eighth grade students in State Middle School 15 Palembang in the 2018/2019 school year. The study sample was 59 students consisting of 30 students from class VIII.9 as the experimental class and 29 students from class VIII.8 as the control class. Samples were taken using Simple Random Sampling techniques. Data was collected through tests of students' mathematical problem solving skills in relation material and functions. The data analysis technique used in this study is the Independent Sample T-Test t-test. The results of the Posttest analysis mean the value of the experimental  class  is  80.34  and  the  average  value  of  the  control  class  is  73.10. Research shows that there is a significant effect of the CORE learning model assisted by Macromedia Flash 8 on mathematical problem solving abilities of students of Palembang State Middle School 15.